2019
DOI: 10.1016/j.pharmthera.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol: To harm or heal

Abstract: Clioquinol, one of the first mass-produced drugs, was considered safe and efficacious for many years. It was used as an antifungal and an antiprotozoal drug until it was linked to an outbreak of subacute myelo-optic neuropathy (SMON), a debilitating disease almost exclusively confined to Japan. Today, new information regarding clioquinol targets and its mechanism of action, as well as genetic variation (SNPs) in efflux transporters in the Japanese population, provide a unique interpretation of the existing phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 80 publications
0
40
0
Order By: Relevance
“…Clioquinol and its derivatives belonging to 8-hydroxyquinoline structural class, have been investigated extensively in basic, translational and clinical studies because of their multiple activities as metal chelators and zinc ionophores, modulating underlying molecular and physiologic switches required for metal homeostatis in vivo [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][36][37][38][39] . Previously, CLQ was used to treat bacterial infections 62 ; however, it was withdrawn from the clinic because of untoward effects of subacute myelo-optic neuropathy (SMON) mostly experienced in Japan in the 1950's 29,62,63 . More recent studies revealed that SMON might be due to other biologic factors and/or pharmacogenetics primarily linked to the Japanese population 29,62,64 .…”
Section: Effects Of Clq and Its Analogues On Rhace2 And Spike (Rbd) Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Clioquinol and its derivatives belonging to 8-hydroxyquinoline structural class, have been investigated extensively in basic, translational and clinical studies because of their multiple activities as metal chelators and zinc ionophores, modulating underlying molecular and physiologic switches required for metal homeostatis in vivo [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][36][37][38][39] . Previously, CLQ was used to treat bacterial infections 62 ; however, it was withdrawn from the clinic because of untoward effects of subacute myelo-optic neuropathy (SMON) mostly experienced in Japan in the 1950's 29,62,63 . More recent studies revealed that SMON might be due to other biologic factors and/or pharmacogenetics primarily linked to the Japanese population 29,62,64 .…”
Section: Effects Of Clq and Its Analogues On Rhace2 And Spike (Rbd) Pmentioning
confidence: 99%
“…Previously, CLQ was used to treat bacterial infections 62 ; however, it was withdrawn from the clinic because of untoward effects of subacute myelo-optic neuropathy (SMON) mostly experienced in Japan in the 1950's 29,62,63 . More recent studies revealed that SMON might be due to other biologic factors and/or pharmacogenetics primarily linked to the Japanese population 29,62,64 . Currently in the clinic, CLQ is approved for use in combination with other agents for treatment of inflammatory skin disorders and fungal infections in some countries 14,65 .…”
Section: Effects Of Clq and Its Analogues On Rhace2 And Spike (Rbd) Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Clioquinol was a registered drug worldwide until its use was associated with the occurrence of subacute myelo-optic neuropathy, a condition primarily endemic to Japan. Today, in view of new information that may explain this phenomenon, clioquinol serves as a drug lead to treat cancer (Perez, Sklar, & Chigaev, 2019).…”
Section: Clinical Potential Of Drugs Targeting Zincmentioning
confidence: 99%